PTH-055 Bougiecap dilatation device: novel endoscopic method for treatment of oesophageal strictures-results from a multicentre study. (June 2019) - Rahman, Imdadur; Boger, Philip; Patel, Praful; Walter, Benjamin; Schmidbaur, Simone; Albers, David; Schumacher, Brigitte; Meining, Alexander
Abstract : Introduction: Benign strictures in the upper GI tract are often treated endoscopically using Savary-Gillard bougie dilatators, which provide tactile feedback. However the drawback to this technique is the lack of direct optic feedback and the need for fluoroscopy during the procedure. A novel device, BougieCap (Ovesco, Germany), allows both tactile and optic feedback of the dilatation procedure without the need for fluoroscopy. The aim of this study was to assess the safety and efficacy of this device in a prospective cohort of patients. Methods: Patients with benign strictures of the oesophagus and with clinical symptoms of dysphagia were recruited from 3 endoscopy centres in the UK and Germany for planned dilatation with the BougieCap. The device is a single use transparent conical cap which is fixed to the tip of the endoscope. It comes in different sizes to facilitate dilatation to varying diameters. Once in place, the endoscope is inserted and positioned in front of the stricture. Under direct vision, pushing forward and rotating with the endoscope enables the conical cap to dilate the mucosa in the area of the stricture by the conversion of longitudinal force into radial force vectors. Dilatation could be repeated sequentially with a larger sized cap if necessary. The primary outcome measure was technical success of dilatation. Secondary outcome measure was improvement in symptoms of dysphagia as assessed by the Dysphagia Handicap index (DHI) before and 14 day after the bougienage procedure and adverse events. Results: 79 patients (M/F 41/38) with benign oesophageal strictures underwent the procedure between February 2018 to January 2019. Aetiology of strictures were peptic 52% (n=40), radiation 25% (n=19), anastomotic 10% (n=8), caustic 7% (n=5), EoE 4% (n=3), post-ESD 3% (n=2). Mean diameter of strictures was 6 mm (±2.9). Endoscopic bougienage was successful in 97.5%. In 2 cases, with a narrow long stricture, bougienage failed because of high resistance at the site of the stricture causing buckling of the endoscope in the pharynx. Symptoms of dysphagia improved after bougienage (53.6 points. d0 v 26.4 points d14, p<0.01). Adverse events were loss of BougieCap in the stomach in 2 cases. No severe adverse events were reported. Conclusions: Endoscopic treatment of benign strictures using the BougieCap enables direct visual and tactile control of the bougienage procedure and therefore of mucosal damage within the area of strictures. This might help to adapt treatment even more precisely to the stricture. Symptoms of dysphagia are improved in short-term follow-up.